Why Hair Needs to Be Long - Nicolas Sihlé (Ateliers d'Anthropologie)
Tibetan tantrists (non-monastic Buddhist practitioners of tantric rituals) attach great importance to keeping their hair long. The importance of tantrists’ hair is particularly striking in Repkong county (northeastern Tibet), which is famous for its large number of tantrists, many of whom wear dreadlocks wound around their heads. This study of the Repkong tantrists’ capillary culture will argue that their hair, at the intersection between the bodily, the social and the political, constitutes an overdetermined religious identity marker. Bromberger’s analytical approach to hair, which focuses primarily on sociological factors such as group belonging or norm vs. marginality, is relevant here, but overlooks key cultural dimensions of the phenomenon. Tibetan notions of embodied divinity and ritual power attached to hair indicate that it is important to include questions about cultural perceptions of the nature of hair and of its relationship with the individuals themselves, or with the beings that can inhabit it.